Optimized Adenoviral Vector That Enhances the Assembly of FMDV O1 Virus-Like Particles in situ Increases Its Potential as Vaccine for Serotype O Viruses - Ziraldo, Micaela; Bidart, Juan E.; Prato, Cecilia A.; Tribulatti, María V.; Zamorano, Patricia; Mattion, Nora; D’Antuono, Alejandra L. (Frontiers in Microbiology, 2020)
Although replication-defective human adenovirus type 5 (Ad5) vectors that express in situ the capsid-encoding regions of Foot-and-mouth disease virus (FMDV) have proved to be effective as vaccines in relevant species for several viral strains, the same result was not consistently achieved for O1/Campos/Brazil/58 strain. In the present study, an optimization of the Ad5 system was explored and proved to enhance the level of capsid proteins expression and their association into virus-like particles (VLPs). Particularly, we engineered a novel Ad5 vector (Ad5[PVP2]OP) carrying the FMDV sequences under the control of an optimized CMV promoter which are inserted in an opposite transcriptional orientation relative to the Ad5 genome. The Ad5[PVP2]OP vaccine candidate also contains the amino acid substitutions S93F/Y98F in the VP2 protein-coding sequence, predicted to stabilize FMD virus particles. Cells infected with the optimized vector showed a ∼14-fold increase in protein expression as compared to cells infected with an unmodified Ad5 vector tested in previous works. Furthermore, amino acid substitutions in VP2 protein allowed the assembly of FMDV O1/Campos/Brazil/58 VLPs. Evaluation of several serological parameters in inoculated mice with Ad5[PVP2]OP vaccine candidate revealed an enhanced vaccine performance, characterized by significant higher titers of neutralizing antibodies, as compared to our previous unmodified Ad5 vector. Moreover, 94% of mice vaccinated with Ad5[PVP2]OP candidate were protected from homologous challenge. These results indicate that both the optimized protein expression and the stabilization of the in situ generated VLPs improved the performance of Ad5-vectored vaccines against FMDV O1/Campos/Brazil/58 strain, and open optimistic expectations to be tested in target animals.